Construction of less neurovirulent polioviruses by introducing deletions into the 5' noncoding sequence of the genome. - Iizuka, N (1989)
Viral attenuation may be due to lowered efficiency of certain steps essential for viral multiplication. For the construction of less neurovirulent strains of poliovirus in vitro, we introduced deletions into the 5' noncoding sequence (742 nucleotides long) of the genomes of the Mahoney and Sabin 1 strains of poliovirus type 1 by using infectious cDNA clones of the virus strains. Plaque sizes shown by deletion mutants were used as a marker for rate of viral proliferation. Deletion mutants of both the strains thus constructed lacked a genome region of nucleotide positions 564 to 726. The sizes of plaques displayed by these deletion mutants were smaller than those by the respective parental viruses, although a phenotype referring to reproductive capacity at different temperatures (rct) of viruses was not affected by introduction of the deletion. Monkey neurovirulence tests were performed on the deletion mutants. The results clearly indicated that the deletion mutants had much less neurovirulence than with the corresponding parent viruses. Production of infectious particles and virus-specific protein synthesis in cells infected with the deletion mutants started later than in those infected with the parental viruses. The rate at which cytopathic effect progressed was also slower in cells infected with the mutants. Phenotypic stability of the deletion mutant for small-plaque phenotype and temperature sensitivity was investigated after passaging the mutant at an elevated temperature of 37.5 degrees C. Our data strongly suggested that the less neurovirulent phenotype introduced by the deletion is very stable during passaging of the virus.